Giant exchange coupling and field-induced slow relaxation of magnetization in Gd2@C79N with a single-electron Gd–Gd bond. Issue 23 (2nd March 2018) - Velkos, G.; Krylov, D. S.; Kirkpatrick, K.; Liu, X.; Spree, L.; Wolter, A. U. B.; Büchner, B.; Dorn, H. C.; Popov, A. A.
Abstract : Single-electron Gd–Gd bond in Gd2 @C79 N results in giant ferromagnetic coupling between local 4f magnetic moments and unpaired electron spin. Abstract : Magnetic properties of the azafullerene Gd2 @C79 N are studied by SQUID magnetometry. The effective exchange coupling constant j Gd, e between the Gd spins and the spin of unpaired electron residing on the single-electron Gd–Gd bond is determined to be 170 ± 10 cm −1 . Low temperature AC measurements revealed field-induced millisecond-long relaxation of magnetization.